Understanding Psychological Dynamics in Consumer Decision-Making Processes in the Digital Marketing Era: A Review - Sudirjo, Frans; Ausat, Abu Muna Almaududi; Suherlan, Suherlan; Azzaakiyyah, Hizbul Khootimah (Jurnal Penelitian Inovatif, 2024)
The digital era has fundamentally transformed marketing paradigms. This shift underscores the need to understand how consumer psychology interacts within the digital environment. This research aims to provide deeper insights into how consumer psychology plays a role in decision-making processes in the digital marketing era, along with its implications for marketing practices. The research methodology employed is a literature review using qualitative approaches and descriptive analysis. Data for the literature review were gathered from Google Scholar for the period 2015-2024. The study findings indicate that in the continually evolving digital marketing era, a profound understanding of consumer psychological dynamics is crucial for business success. Factors such as perception, attitude, motivation, and emotion play key roles in consumer decision-making processes. Marketers need to pay attention to how digital content and interactions influence consumer preferences and behaviors. Additionally, external factors such as social and cultural contexts also shape consumer psychological dynamics.